Analysis and Simulation of Dynamic Vision in the City: A Computer-Aided Cinematic Approach - Xu, Fang (Enquiry The ARCC Journal for Architectural Research, 2019)
This paper proposes a computer-aided Dynamic Visual Research and Design Protocol for environmental designers to analyze humans' dynamic visual experiences in the city and to simulate dynamic vision in the design process. The Protocol recommends using action cameras to collect massive dynamic visual data from participants' first-person perspectives. It prescribes a computer-aided visual analysis approach to produce cinematic charts and storyboards, which further afford qualitative interpretations for aesthetic assessment and discussion. Employing real-time 3D simulation technologies, the Protocol enables the simulation of people's dynamic vision in designed urban environments to support evaluation in design. Detailed contents and merits of the Protocol were demonstrated by its application in the Urbanscape Studio, a community participatory design course based at Watertown, South Dakota.